PENINGKATAN KEPEDULIAN LINGKUNGAN DI KALANGAN MAHASISWA TERHADAP GREEN MARKETING - Shankae, Arvin; Masnita, Yolanda (Universitas Of Surakarta, 2023)
Social media and campaigns among students are quite influential in making students more equitable in protecting the environment and using environmentally friendly products. This study aims to analyze environmental problems that can affect the life of all living things. The instrument of this research is using a questionnaire created using a Google form that is distributed online. Respondents in this study were the age group of 17 years and over. This study contributes to this test of consistency between environmental concern and pro-env intention variables.